An intermolecular pyrene excimer-based ratiometric fluorescent probes for extremely acidic pH and its applications. (March 2020) - Liu, Tian; Huang, Zijie; Feng, Ruihong; Ou, Zhiqi; Wang, Sha; Yang, Liting; Ma, Li-Jun
Abstract: Fluorescent ratiometric probes based on monomer/excimer of pyrene group are often used to detect cations. However, only a few pyrene-containing ratiometric pH probes have been reported so far, and almost all of them produce intramolecular pyrene excimer. In this work, three new ratiometric fluorescent pH probes based on intermolecular pyrene excimer, pyrene-1-carboxamide (1 ), N-(2-hydroxyethyl)pyrene -1-carboxamide (2 ) and N, N-bis(2-hydroxyethyl) pyrene-1-carboxamide (3 ), were synthesized. These probes, 1, 2, and 3, have p K a value of 1.93, 1.85 and 2.07, respectively, and can fluorescently determine the pH value of the extremely acidic aqueous solution with a detection range of about 1.0–2.5. When the pH value was decreased from 2.5 to 1.0, these probes showed a ratiometric fluorescent response signal due to the conversion of monomer/excimer of pyrene group. Therefore, intermolecular excimer of the pyrene group from these probes can be produced in extremely acidic environment. Further tests show that these probes have potential as excellent pH fluorescent probes, with high sensitivity, fast response time, good photostability, strong anti-ion interference ability and high repeatability, etc. The applicability of these probes was demonstrated with environment water samples. In addition, fluorescent pH test paper was successfully developed, which can monitor pH values in the solution through pH-related change of fluorescent color of the probes. Graphical abstract: The ratiometric fluorescent probes based on intermolecular pyrene excimer, 1, 2 and 3, can detect pH value of the extremely acidic water environment (distilled water, tap water and Zhujiang River water) with high sensitivity, fast response time, good photostability, strong anti-ion interference ability and good repeatability. Image 1 Highlights: Probes 1-3 can ratiometric fluorescent measurepH valuein the range of about 1.0–2.5. Probes 1 -3 showhigh sensitivity, fast response timeandgood photostability. Probes 1 -3 showstrong anti-ion interference ability andgood repeatability. Probes 1-3 can be used in thedetectionpH value ofthe environmental water samples. Probes 1-3 can be used in the productionofpH test paper.